Application of social ecological model to Taiwanese end-of-life communication and healthcare planning. Issue 5 (October 2020) - Huang, Ya-Ling; Yates, Patsy; Thorberg, Fred Arne; Wu, Chiung-Jung (Jo)
ABSTRACT: Background: Cultural and social backgrounds shape how people regard health, illness and death, and also play a significant role in end-of-life (EOL) decision-making in the face of uncertainty and distress. EOL communication and planning can be complex in a society where families play an important role in decision-making for EOL care in Taiwan. Aim: This study aimed to identify the significance of cultural, community, interpersonal and individual determinants of EOL communication and healthcare planning. Methods: A social ecological model was applied to underpin the study. A random sample of 2000 adults aged 20 years or above was selected from the electoral roll in a metropolitan area in southern Taiwan. Adults were told that if they did not wish to participate in the study, they could either return a non-participation form or not complete the questionnaires. Hierarchical multiple regression analyses were used to determine the significance of different societal levels of factors on EOL communication and healthcare planning. Findings: Four hundred and seventy-four valid questionnaires were returned. Hierarchical multiple regression analyses revealed that the models of modified Measures of Public Preferences ( p < .0001) were significant, with 22.7% of variance in facilitation, 81.9% of variance in content and 22.9% of variance in support being explained by variables at cultural, community, interpersonal and intrapersonal levels. The model of Advance Directives Attitude Survey ( p < .0001) was significant with 25.6% of variance being explained by variables at cultural, community, interpersonal and intrapersonal levels. Discussion: This study offers empirical evidence embedded within a social ecological perspective of the significance of cultural, social and contextual factors on individuals' preferences for EOL communication and healthcare planning. Conclusion: Such information is important to enable health professionals to prepare individuals and their families for dealing with challenges related to EOL communication and healthcare.